Investigating Students’ Silence during Synchronous Virtual Classroom: A Case Study - Dela Rahmawati; Yuyus Saputra; Fera Sulastri (Siliwangi University, 2022)
This current study explores the silent behavior of students within a synchronous virtual classroom. It focuses on investigating the factors affecting students’ silence in the synchronous virtual classroom from the students’ perception. This study used a descriptive case study as the research design. This study used semi-structured interviews as the data collection. A semi-structured interview was asked to five silent students in the synchronous virtual classroom. Then, the data were analyzed using thematic analysis (Braun and Clarke, 2006). The findings indicate various causes of students’ silence in the synchronous virtual classrooms: lack of confidence, describing comprehension by silence, lack of knowledge, lack of English proficiency, being a good listener and showing respect, lack of preparation for learning, unsuitable teaching style, and technical issues. Keywords: students’ silence, synchronous virtual classroom, case study